Association between PTSD and Cognitive Performance: A Longitudinal Twins Study. (20th December 2022) - Kulshreshtha, Ambar; Shah, Amit; Ko, Yi‐An; Goldberg, Jack; Smith, Nicholas; Jajeh, Nour; Ahmed, Hashir; Marof, Biwar; Murrah, Nancy; Shallenberger, Lucy; Driggers, Emily; Bremner, Douglas; et al.
Abstract: Background: Posttraumatic Stress Disorder (PTSD) is a chronic psychiatric condition that develops after exposure to life‐threatening events. The negative impact of PTSD on a person's emotions and behavior can have long‐term deleterious effects on cognitive performance. The association between PTSD and cognition however can be confounded by unmeasured factors such as shared genetic and environmental factors. Twin studies allow us to explore this potential causal pathway by controlling for genetic and familial confounding. Methods: We examined 77 male monozygotic and 47 dizygotic twin pairs from the Vietnam Era Twin Registry in two examinations approximately 12 years apart. At both visits, we obtained information regarding demographic data, medical history, diagnosis of PTSD and cognitive tests. Memory and learning were measured by Trail making tests, Wechsler Memory Scale (Immediate and Delayed Memory tests and Visual Reproductive Test). Linear mixed‐effect regression models were used to examine the association between PTSD and cognitive tests accounting for twin pairing. Analysis was performed by treating twins as individuals and considering within twin pair differences (among twin pairs discordant for PTSD). Results: The mean age was 55 years (SD 3.0) at baseline, 96% were White, and 60% monozygotic twins. Lifetime history of PTSD was not associated with cognitive measures at baseline. At follow‐up, the mean age was 67.9 years (SD 2.5). In twins considered as individuals lifetime history of PTSD was associated with worse performance on Trails A (β = 4.9, 95% CI 8.6, 1.3, p‐value = 0.008) and Trails B (β = 14.6, 95% CI 26.8, 2.4, p‐value = 0.019). After adjusting for demographics, cardiovascular and behavioral risk factors, these associations persisted (Trails A, β = 5.4, 95% CI 9.4, 1.4, p‐value = 0.009; Trails B, β = 14.1, 95% CI 26.9, 1.2, p‐value = 0.032). The within‐pair estimates were similar to individual estimates. There was no association with Wechsler immediate or delayed story recall or Visual Reproductive Test. In stratified analyses, the results were similar by zygosity. Conclusions: Lifetime history of PTSD is associated with poor cognitive performance, primarily in the executive function domain, which manifests at older age. This association is not confounded by shared genetic and other familial factors.